Simulation- Based Training for Resuscitation in Cardiac Arrest - Archita Patil; Sandeep Kadam; Arati Jadhav (Medical Research and Its Applications Vol. 9, 2024)
Simulation technology was first used in the aviation sector, but it has now found application in the medical field too. Simulation in medical education can be used to train students in evidence-based medical practices to improve patient outcomes. We planned a simulation-based training program with the primary objective of training students to demonstrate competency in cardiopulmonary resuscitation. The secondary objective was to assess students’ satisfaction with the training and record their feedback. Computer-based data from the simulator was considered to note the time to initiate CPR, the time to defibrillate, the rate and depth of chest compression and the efficacy of ventilation. Simulation-based training session in the management of cardiac arrest helps to increase the knowledge, psychomotor skills and confidence level of medical post-graduate students.